2016
DOI: 10.1111/jvec.12189
|View full text |Cite
|
Sign up to set email alerts
|

Vertical oviposition activity of mosquitoes in the Atlantic Forest of Brazil with emphasis on the sylvan vector, Haemagogus leucocelaenus (Diptera: Culicidae)

Abstract: This study aimed to assess the vertical patterns of oviposition and temporal changes in the distribution of mosquito species in an area of the Atlantic Forest in Rio de Janeiro State, Brazil, and in particular, the behavior and oviposition of potential yellow fever virus vectors. Mosquito samples were collected from the Ecological Reserve Guapiaçu (REGUA, Brazil), which includes a somewhat disturbed forest, with a large diversity of plants and animals. In all, 5,458 specimens (ten species from seven genera) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
36
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 23 publications
(23 reference statements)
4
36
0
1
Order By: Relevance
“…Alencar et al (2016) [21] have reported three epidemiologically important mosquito species in the transmission of arboviruses ( Hg. leucocelaenus, Hg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alencar et al (2016) [21] have reported three epidemiologically important mosquito species in the transmission of arboviruses ( Hg. leucocelaenus, Hg.…”
Section: Discussionmentioning
confidence: 99%
“…The traps were placed at a height that varied between 2 and 10 m above soil level. Details on the use and manufacturing of the ovitraps can be found in studies previously done [20,21]. The paddles in the traps were examined every two weeks to detect and quantify the eggs.…”
Section: Methodsmentioning
confidence: 99%
“…equinus Theobald, 1903, which can even be found in some southern parts of the Nearctic region 2 . These are mainly wild, diurnal, and acrodendrophic mosquitoes inhabiting primarily dense forest and gallery areas 3 .…”
mentioning
confidence: 99%
“…In Diptera, it has been widely used to answer questions mainly related to population studies 6 . A recent study of Culex mosquitoes from the state of Rio de Janeiro showed the effects of seasonal variations on phenotypic variations using this tool 3 .…”
mentioning
confidence: 99%
See 1 more Smart Citation